Development of a spontaneous model of renal interstitial fibrosis in NOD/SCID mice: Aging-induced pathogenesis. - Lihua Qiu; Zhaoxia Ma; Jinyan Li; Zhen Wu; Longmei Dai; Ruimin Long; Linlin Hu; Jianxiu Sun; Min Hu; Yanjiao Li (PLoS ONE)
Renal interstitial fibrosis, a condition prevalent in aging humans and animals, is closely linked to the eventual development of renal failure. Establishing an animal model that exactly replicates the pathogenesis of renal interstitial fibrosis induced by natural aging in humans is crucial for advancing mechanistic studies and testing antifibrotic therapies. Implanted allogeneic or xenogeneic cells are cleared by the immune system when stem cell therapy is applied in nonimmunodeficient animal fibrosis models, affecting the effect of the intervention and making it difficult to demonstrate the survival, proliferation, differentiation, or secretion of the delivered autologous human-derived cells. This study effectively developed a model of spontaneous renal interstitial fibrosis linked to natural aging in 43-week-old NOD/SCID mice. Compared with those of 12- and 32-week-old mice, the kidneys of the model mice exhibited prominent fibrosis characteristics, accompanied by numerous fibrous septa and collagen deposition, increased COL1A1 expression, and decreased MMP9 expression. SA-β-gal activity and P21 gene expression levels increased, confirming renal cell senescence in the model mice. Additionally, an increase in α-SMA staining indicated an increase in epithelial-mesenchymal transition. More importantly, we observed TGF-β-SMAD3 pathway activation, mitochondrial dysfunction, decreased antioxidant capacity, oxidative stress, and an enhanced inflammatory response in the model group, consistent with renal interstitial fibrosis in elderly individuals. In this comprehensive investigation, we successfully developed a spontaneous mouse model of renal interstitial fibrosis and revealed the molecular pathways contributing to increased susceptibility to kidney injury and renal fibrosis in elderly individuals.